Data on food insufficiency status in South Africa: Insight from the South Africa General Household Survey - Omotayo, Abiodun Olusola; Ogunniyi, Adebayo; Aremu, Adeyemi Oladapo (Elsevier, 2019)
Food insecurity or insufficiency, among other factors, is triggered by structural inequalities. Food insecurity is an inflexible problematic situation in South Africa. The country has a custom of evidence-based decision making, stocked in the findings of generalized national household surveys. Conversely, the deep insights from the heterogeneity of the sub-national analysis remain a principally unexploited means of understanding of the contextual experience of food insecurity or insufficiency in South Africa. The data present the food insufficiency status with special focus on adult and children. The data also reveal the adult and children food insufficiency status across the provinces in South Africa. The data contains socioeconomic and demographic characteristics as well the living condition and food security status of the households.